2008
DOI: 10.1002/chin.200828249
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Structure—Activity Relationship of trans‐Resveratrol and Its Analogues.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 0 publications
0
35
0
1
Order By: Relevance
“…Например, катехольная группа играет ключевую роль в противорадикальной активности [7], и, в нашем случае, обеспечивает более эффективное образование [M -2H] -и H 2 в пицеатанноле. Последний, действи-тельно, является более эффективным антиоксидантом, чем ресвератрол [44][45][46][47], несмотря на то, что наблюдае-мые эффекты полифенольных соединений в организме очень многогранны, и определяются множеством факто-ров, как например, биодоступностью и эффективностью усвоения.…”
Section: Discussionunclassified
“…Например, катехольная группа играет ключевую роль в противорадикальной активности [7], и, в нашем случае, обеспечивает более эффективное образование [M -2H] -и H 2 в пицеатанноле. Последний, действи-тельно, является более эффективным антиоксидантом, чем ресвератрол [44][45][46][47], несмотря на то, что наблюдае-мые эффекты полифенольных соединений в организме очень многогранны, и определяются множеством факто-ров, как например, биодоступностью и эффективностью усвоения.…”
Section: Discussionunclassified
“…Thus it was suggested that the cytotoxicity of Pte and its analogues depends significantly on the structural determinants, which are double bond and methylated phenolic hydroxyl (Supplementary Fig. 1: a and e) (34). Therefore Pte can serve as a lead compound to derive other analogues with higher therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The following elements of a compound chemical structure have the essential meaning for the biological activity of RSV and its derivatives; the number and position of hydroxyl groups, the presence of intramolecular hydrogen bonds, spatial isomerism and double bonds [28].…”
Section: The Resveratrol Analoguesmentioning
confidence: 99%